Spatial transcriptomic analysis delineates epithelial and mesenchymal subpopulations and transition stages in childhood ependymoma. Issue 4 (10th October 2022) - Fu, Rui; Norris, Gregory A; Willard, Nicholas; Griesinger, Andrea M; Riemondy, Kent A; Amani, Vladimir; Grimaldo, Enrique; Harris, Faith; Hankinson, Todd C; Mitra, Siddhartha; Ritzmann, Timothy A; Grundy, Richard R; et al.
Abstract: Background: The diverse cellular constituents of childhood brain tumor ependymoma, recently revealed by single cell RNA-sequencing, may underly therapeutic resistance. Here we use spatial transcriptomics to further advance our understanding of the tumor microenvironment, mapping cellular subpopulations to the tumor architecture of ependymoma posterior fossa subgroup A (PFA), the commonest and most deadly childhood ependymoma variant. Methods: Spatial transcriptomics data from intact PFA sections was deconvoluted to resolve the histological arrangement of neoplastic and non-neoplastic cell types. Key findings were validated using immunohistochemistry, in vitro functional assays and outcome analysis in clinically-annotated PFA bulk transcriptomic data. Results: PFA are comprised of epithelial and mesenchymal histological zones containing a diversity of cellular states, each zone including co-existing and spatially distinct undifferentiated progenitor-like cells; a quiescent mesenchymal zone population, and a second highly mitotic progenitor population that is restricted to hypercellular epithelial zones and that is more abundant in progressive tumors. We show that myeloid cell interaction is the leading cause of mesenchymal transition in PFA, occurring in zones spatially distinct from hypoxia-induced mesenchymal transition, and these distinct EMT-initiating processes were replicated using in vitro models of PFA. Conclusions: These insights demonstrate the utility of spatial transcriptomics to advance our understanding of ependymoma biology, revealing a clearer picture of the cellular constituents of PFA, their interactions and influence on tumor progression. Graphical Abstract: